Cultivar selection can increase yield potential and resource use efficiency of spring maize to adapt to climate change in Northeast China - Zheng-e SU; Zhi-juan LIU; Fan BAI; Zhen-tao ZHANG; Shuang SUN; Qiu-wan HUANG; Tao LIU; Xiao-qing LIU; Xiao-guang YANG (Journal of Integrative Agriculture)
Northeast China (NEC) is one of the major maize production areas in China. Agro-climatic resources have obviously changed, which will seriously affect crop growth and development in this region. It is important to investigate the contribution of climate change adaptation measures to the yield and resource use efficiency to improve our understanding of how we can effectively ensure high yield and high efficiency in the future. In this study, we divided the study area into five accumulated temperature zones (ATZs) based on growing degree days (GDD). Based on the meteorological data, maize data (from agro-meteorological stations) and the validated APSIM-Maize Model, we first investigated the spatial distributions and temporal trends of maize potential yield of actual planted cultivars, and revealed the radiation use efficiency (RUE) and heat resource use efficiency (HUE) from 1981 to 2017. Then according to the potential growing seasons and actual growing seasons, we identified the utilization percentages of radiation (PR) resource and heat resource (PH) for each ATZ under potential production from 1981 to 2017. Finally, we quantified the contributions of cultivar changings to yield, PR and PH of maize. The results showed that during the past 37 years, the estimated mean potential yield of actual planted cultivars was 13 649 kg ha–1, ranged from 11 205 to 15 257 kg ha–1, and increased by 140 kg ha–1 per decade. For potential production, the mean values of RUE and HUE for the actual planted maize cultivars were 1.22 g MJ–1 and 8.58 kg (°C d)–1 ha–1. RUE showed an increasing tendency, while HUE showed a decreasing tendency. The lengths of the potential growing season and actual growing season were 158 and 123 d, and increased by 2 and 1 d per decade. PR and PH under potential production were 82 and 86%, respectively and showed a decreasing tendency during the past 37 years. This indicates that actual planted cultivars failed to make full use of climate resources. However, results from the adaptation assessments indicate that, adoption of cultivars with growing season increased by 2–11 d among ATZs caused increase in yield, PR and PH of 0.6–1.7%, 1.1–7.6% and 1.5–8.9%, respectively. Therefore, introduction of cultivars with longer growing season can effectively increase the radiation and heat utilization percentages and potential yield.